The Role of Non-penetrative Partnered Sex Activities in the Associations Among Erectile Difficulties, Sex and Relationship Satisfaction in Men Aged 50 - Ševčíková, Anna; Gottfried, Jaroslav; Gocieková, Veronika; Gore-Gorszewska, Gabriela; Blinka, Lukas; Kotík, Jan (International journal of sexual health, 2023)
OBJECTIVES: This study examined the associations among erectile difficulties, sexual satisfaction, and relationship satisfaction, and whether there is a buffering effect of non-penetrative partnered sex on relationship satisfaction in men aged 50+ who report erectile difficulties. METHODS: An analysis of survey data from 431 Czech men (aged 50-96, Mdn = 64). RESULTS: Engagement in non-penetrative partnered sex did not moderate the relationship between erectile difficulties and sexual and relationship satisfaction, but it was linked to higher sexual and relationship satisfaction. CONCLUSIONS: The buffering effect of non-penetrative practices for the link between erectile difficulties and relationship satisfaction has not been supported.
Keywords: sexual health; relationship satisfaction; erectile difficulties; Aging